Theoretical study on the mechanism of stick-slip instability occurrence on deep coal-rock structure - Zhang, Zhenpei; Yang, Guanyu; Lü, Yulei; Chen, Yulong; Yang, Chao; Zheng, Jianwei (Frontiers in Earth Science, 2024)
Dynamic disasters seriously threaten the safety and effectiveness in deep mining. The mechanism of stick-slip instability occurrence on the deep coal-rock structure was studied in this paper through analyzing the occurrence condition of stick-slip in the weak surface and discussing the friction constitutive of the coal-rock structure. The result indicated that the grinding slip and the soft interlayer formation occurred in weak plane in the coal-rock structure in the process of diagenesis and strata movement, which is more likely to satisfy the stick-slip condition and then trigger dynamic disaster. Based on the mechanism study of coal-rock structure failure caused by stick-slip, it is proposed that the horizontal compression pulse caused by local stick-slip in coal seam could lead the layer-crack and fly out with the broken fragments. At the same time, it is pointed out that the scattering effect of the plane compression pulse in the propagation process induces the serial sliding instability of the coal-rock structure in many places, forming a large range of dynamic disasters. By means of numerical simulation of coal bump accident in a roadway in Yima Coal Mines, the dynamic process of sliding-slip instability of coal and rock mass is inverted, and the mechanism of sliding-slip instability of coal and rock structure is verified.